Alone in Eden: Care Aides' Perceptions of Consistent Assignments. (March 2015) - Andersen, Elizabeth; Spiers, Jude
The Eden Alternative® is a philosophy of care and transformational model aimed at increasing quality of life for nursing home residents by enhancing institutional environments and restructuring delivery of care. Restructured care consists of three fundamental components: resident care provided primarily by care aides, enhanced responsibilities for care aides, and consistent assignment of residents to care aides. Researchers have focused on resident and family satisfaction with the model, but there is limited research evaluating the impact of the model on nursing home employees. This article is focused on their experiences. Convenience and purposive sampling were used to recruit 22 care aides from five nursing homes in a western Canadian city. Experiential interview data were collected and analyzed utilizing constant comparison to identify common themes. Although care aides initially welcomed the restructuring, they described gradually becoming overwhelmed by the work, confined by consistent assignments, and isolated from colleagues and other residents.